Follow up imaging of oral, oropharyngeal and hypopharyngeal cancer patients: Comparison of PET-CT and MRI post treatment. Issue 7 (July 2020) - Breik, Omar; Kumar, Anand; Birchall, James; Mortimore, Sean; Laugharne, David; Jones, Keith
Abstract: There is currently no consensus as to the ideal timing, frequency and modality of imaging for follow up of head and neck cancer patients. The aim of this study was to analyze the diagnostic accuracy of PET-CT versus MRI, and imaging at 3 versus 6 months for follow up of head and neck cancer patients treated with curative intent with no clinical signs of treatment failure. Materials and methods: A retrospective study was performed for all head and neck cancers treated with curative intent at the Royal Derby Hospital. Data collected included demographic information, site of primary cancer, staging, treatment provided, type of follow up imaging performed and results of follow up imaging. Inclusion in the study was for oral, oropharyngeal and hypopharyngeal cancers treated with curative intent, asymptomatic patients, those who have had follow up imaging within 6 months of treatment, and those followed up for at least 2.5 years since treatment. Results: A total of 140 patients were included in the study. 25% of patients had evidence of recurrent/metastatic disease on imaging, 60% of which were identified within 6 months post treatment. The majority (60%) of failures were due to distant metastases. The sensitivity and specificity of both MRI and PET-CT was higher at 6 months post-treatment compared to 3 months post-treatment. Overall the sensitivity and specificity for PET-CT and MRI within 3–6 months post treatment were 94.7% and 83.5% and 60% and 85.7% respectively for identifying treatment failure. Conclusion: Follow up Imaging at 6 months post treatment is more likely to accurately identify treatment failures with fewer false positives than imaging at 3 months. PET-CT is preferable to MRI for identifying post treatment locoregional and distant treatment failure. Highlights: Follow up imaging protocols are highly variable between centres. Rate of recurrence/distant metastatic disease was approximately 25% in this study. Regardless of whether an MRI or a PET-CT is performed, Imaging at 6 months post treatment has a better sensitivity and specificity compared to imaging at 3 months post-treatment. In patients with oral, oropharyngeal and hypopharyngeal cancers with no clinical symptoms of recurrent disease, follow up PET CT is more sensitive than MRI in identifying treatment failure, both locoregional and distant disease.